Differential interactions of α-synuclein conformers affect refolding and activity of proteins. (11th November 2022) - Bagree, Gayatri; Srivastava, Tulika; Mahasivam, Sanje; Sinha, Meetali; Bansal, Vipul; Ramanathan, Rajesh; Priya, Smriti; Sharma, Sandeep K
Abstract: The accumulation of protein aggregates as intracellular inclusions interferes with cellular protein homeostasis leading to protein aggregation diseases. Protein aggregation results in the formation of several protein conformers including oligomers and fibrils, where each conformer has its own structural characteristic and proteotoxic potential. The present study explores the effect of alpha-synuclein (α-syn) conformers on the activity and spontaneous refolding of firefly luciferase. Of the different conformers, α-syn monomers delayed the inactivation of luciferase under thermal stress conditions and enhanced the spontaneous refolding of luciferase. In contrast, the α-syn oligomers and fibrils adversely affected luciferase activity and refolding, where the oligomers inhibited spontaneous refolding, whereas a pronounced effect on the inactivation of native luciferase was observed in the case of fibrils. These results indicate that the oligomers and fibrils of α-syn interfere with the refolding of luciferase and promote its misfolding and aggregation. The study reveals the differential propensities of various conformers of a pathologically relevant protein in causing inactivation, structural modifications and misfolding of other proteins, consequently resulting in altered protein homeostasis. Graphical Abstract: